Improvement of Hydrophobicity and Dimensional Stability of Thermally Modified Southern Pine Wood Pretreated with Oleic Acid - Yuan Zhu; Wang Wang; Jinzhen Cao (BioResources, 2014)
The present work used a combined approach of oleic acid (OA) impregnation and thermal modification to improve the hydrophobicity and dimensional stability of southern pine (Pinus spp.). The wood samples were first treated with OA at a concentration of 5 or 10%, and then underwent thermal modification at 160, 180, or 200 °C. Thereafter, the water-related properties of modified wood including water absorption (WA), equilibrium moisture content (EMC), and volumetric swelling (VS) were investigated. Alterations in cell wall structure and chemical components were analyzed by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), based on the mechanisms discussed. While the results showed that both OA-treatment and thermal modification can each improve the water repellency and dimensional stability of wood, the combined system proved to be more effective. The synergistic increase of water-related properties was assumed to be caused by OA increasing the hydrophobicity of thermally modified wood as well as accelerating the decomposition of hydrophilic wood components during thermal modification. This assumption was supported by both SEM and FTIR results. Therefore, this research provides an approach for improving the accessibility to the energy-efficient thermal modification.